Domestic violence in pregnancy - Riaz, Saher; Iqbal, Hafiza Iqra; Riaz, Anam; Asghar, Saman; Shaukat, Shysta; Rasool, Saba (Journal of the Pakistan Medical Association, 2026)
A descriptive cross-sectional study was conducted at the Department of Gynaecology and Obstetrics, Services Hospital, Lahore, from January 15, 2023, to July 14, 2023, with the aim to evaluate the prevalence of domestic violence among pregnant women attending the antenatal clinic at a tertiary care hospital in Lahore, Pakistan. A total of 150 pregnant women aged 18–40 years, with gestational ages of 8–37 weeks, were included using non-probability consecutive sampling. Data was collected through structured interviews and analysed using the Statistical Package for the Social Sciences (SPSS) version 25. The prevalence of domestic violence was in 40(26.67%), with a significant association with the husband’s occupation (p=0.028). No significant associations were observed with maternal age, gestational age, body mass index (BMI), education level, or socioeconomic status. Regular screening for domestic violence during antenatal visits is essential to identify and support the affected women and improving maternal and foetal health outcomes. Keywords: Domestic violence, Pregnancy, Antenatal care, Maternal health, Intimate partner violence (MeSH terms).